Comparative analysis of RNA-Seq data reveals adventitious root development is mediated by ChIFNα in lotus japonicus. Issue 1 (1st January 2021) - Yang, Shimei; Ma, Siyu; Qiu, Riguang; Guang, Qiao; Lv, Yun; Dong, Yaping; Wu, Jiahai; Song, Li
Abstract: The formation of adventitious roots (ARs) plays an important role in grass growth and production. Chicken alpha interferon ( ChIFNα ) is an animal glycoprotein with broad activities of immune control, gene induction, growth and development regulation. ChIFNα gene was transformed to Lotus japonicus and its expression was found to promote AR development. The primordia formation occurred 3–5 days earlier, and more root hairs appeared in the transgenic plants (TP) than in the wild-type parents (WT). Data of RNA sequences from TP and WT in vitro hydroponic culture were analyzed. Overall, the intersection of the differentially upregulated genes at 0–12 days included 278 genes in TP and 244 genes in WT plants. Gene Ontology analysis indicated that the differentially expressed genes (DEGs) in TPs were enriched in response to biotic stimulus, metabolic process, sucrose transport, carbon fixation and signal transduction. Further, Kyoto Encyclopedia of Genes and Genomes enrichment analysis found carbon metabolism, carbon fixation in photosynthetic organisms and photosynthesis enriched in TPs. Co-expression analysis of the DEGs showed that 35 and 18 transcription factors (TFs) were involved in ARs formation in TP and WT plants, respectively. However, the TFs C3H and C2C2-GATA showed the opposite regulatory pattern with ChIFNα expression. Together, these data suggest that ChIFNα promotes AR development by modulating specific pathways and TFs. These results provide new insight into the mechanism by which animal interferon modulates plant growth and lays the foundation for cultivating new forage germplasm using animal cytokines.